Managing IT/Community Partnerships in the 21st Century
DOI: 10.4018/978-1-930708-33-4.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Service-Learning Partnerships in the Information Systems Curriculum

Abstract: Service-learning partnerships involve students taking part in structured community service that relates to their academic course experience. Students who major in information systems are increasingly being provided with real-world experiences. These real-world experiences offer numerous benefits. Students can immediately apply their course knowledge to real-world situations. Students can gain the experience of grappling with political, social, and ethical issues in a workplace setting. In addition, students ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…These findings are consistent with the research done by Saulnier (2005) and acts as supporting evidence to the belief that service-learning may be an effective pedagogy in IS (Lazar & Lidtke, 2002) as it "improve[s] the achievement of learning objectives" (Andrews, 2007, p. 23).…”
Section: Skill-set Developmentsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with the research done by Saulnier (2005) and acts as supporting evidence to the belief that service-learning may be an effective pedagogy in IS (Lazar & Lidtke, 2002) as it "improve[s] the achievement of learning objectives" (Andrews, 2007, p. 23).…”
Section: Skill-set Developmentsupporting
confidence: 89%
“…According to Lazar and Lidtke (2002), service-learning may be incorporated into several different IS courses so that students may learn more about database design, online communities, networking, and human-computer interaction. Students may also provide training or create user manuals.…”
Section: Methodsmentioning
confidence: 99%
“…Put another way, if students submit materials that are sub-par for an assignment, the student may simply accept a grade of C or D. But if the project is being viewed and used by an outside audience, the student may not only feel more motivated, but the professor may say that the student simply must re-do the work until the work is of a satisfactory nature. Another benefit of community-based projects is that often, students find it harder to cheat, since you simply can't submit work from a previous class [8]. At the same time, often determining the individual level of effort within a group of students can be challenging, and it does take a lot of coordination time on behalf of the professor [10].…”
Section: Benefits Of Community-based Service Projectsmentioning
confidence: 98%
“…It is important to have clear roles, responsibilities, and deadlines for both students and any community partners [8]. It is further suggested that the students, community partner, and professor sign a "contract" specifying the roles, which also specifies deadlines for communication, work, and deliverables.…”
Section: Success Factors For Community-based Projects In Undergraduatmentioning
confidence: 99%
“…Students build and improve their technical skills and capabilities, and build a greater understanding of the systems development lifecycle (e.g., Godfrey, 1999;Guthrie and Navarrete, 2004). Lazar and Lidtke (2002) found that servicelearning initiatives give students an opportunity to experience user issues in a real-world environment, hence improving their ability to address political, communication, and ethical issues. Homkes (2008) argues that since service-learning is experiential learning and thus, allows for a more holistic and lasting learning by the students.…”
Section: Introductionmentioning
confidence: 99%